Ethnographic research data on the criminalisation of solidarity work with migrants in France and Morocco, 2022-2023 - Bachelet, Sébastien (UK Data Service, 2024)
This ethnographic project aims to examine criminalizing and illegalizing processes targeting pro-migration activists and other citizens (e.g. volunteers, practitioners) in Morocco and France. The study investigates the competing ways in which ‘crimes of solidarity’ mobilise discourses and practices of solidarity, citizenship, and illegality in Morocco and France. The data collection examines how state repression of pro-migration activists and other ‘citizens’, who are often conflated with smugglers and accused of aiding irregular migrants, sheds light on the shifting and contested legal, moral and political boundaries between ‘irregular migrants’ and ‘citizens’. The recent focus on the figure and experience of ‘the migrant’ has enriched scholarly engagements with the construction of migrant illegality, irregular migrant political agency, and the entanglements of humanitarianism and security. Our project expands these conversations by exploring how migration politics target and affect not just migrants but also citizens. This shift is necessary in order to examine the far-reaching bordering practices and contested politics of exclusion beyond inter-state boundaries and the precarious lives of irregular migrants. We investigate how migration politics in France and Morocco are shifting the political agency and subjectivity of citizens who face (the threat of) prosecution from state authorities at the border and beyond. This has been achieved through participant observation and informal interviews with activists, artists, community leaders, NGO practitioners, funders, and other relevant professionals in Morocco and France. Themes discussed during conversations included : participants’ opinions about the politics of migration in Morocco/France; their history of activism and other engagement around migration; the motivations behind their engagement; the difficulties and obstacles they have faced in their activities and engagement over migration etc. The project has generated original insights into how hostile migration politics that selectively manage, stop, deter, and control forms of mobility also target individuals and organisations providing forms of support, assistance, aid to migrant people. The project has shed light on how state authorities in France and Morocco deploy indirect, opaque, and insidious forms of harassment to intimidate ‘subversive solidarity actors’: citizens engaging in acts of solidarity with migrant people who publicly or covertly engage in a critical stance on migration control policies and practices. This research emphasises the importance of taking the policing of solidarity actors into account to understand the policing of migration more broadly, detailing how the racist and gendered policing of migrant people bleeds into the disciplining of those who support them. While attention to citizen solidarity has focused on European countries, the phenomenon is also visible in countries south of the Mediterranean. Spectacular trials have made the headlines. Our research findings shed light on the workings of less spectacular modes of criminalisation that target solidarity workers in the intimacy of their everyday lives, threatening their sense of security through opaque surveillance, attacks on their emotions, employment prospects and family life. We conceptualise this mode of criminalisation as ‘insidious harassment’, examining the entanglement of geopolitics, emotions, and the intimate at these migration pressure points. Without decentring migrants as the primary targets of violent bordering, it broadens our understanding of these regimes by drawing attention to the ways in which they viscerally target those who work to protect the rights of migrant people. The project’s findings highlight how forms of criminalisation range widely, from the explicit and physical to the intimate and psychological; from the formal to the informal, the banal to the spectacular. The findings reveal that states invest considerable resources - money, human resources (official & unofficial) and time - in seeking to inflict a sense of constant surveillance and discomfort on solidarity actors. Many of the people we spoke to suspected that these indirect and opaque forms of state violence represent a way to protect the appearance and reputation of these states as rights-respecting, while in fact they pursue a dedicated campaign of trying to harass migrant people and those who support them into submission. The effects of insidious harassment are multiple: they are financial, administrative, emotional, psychological, physical and sometimes legal. Beyond just impacting practices of solidarity, they work to target solidarity actors on a moral and on practical levels, with repercussions on their work, family and social lives. This constitutes a protracted and everyday pressure that often works to disrupt solidarity actors’ sense of safety within and trust of the authorities and nation state. However, achieving an overview and in-depth understanding of these modes of policing and how they play out may contribute to reducing these effects. This research project has also shed light on how in contexts where repression is constantly squeezed and solidarity actors face damaging state practices, their commitment to rectifying social injustices and wrongs is also galvanised. As irregular migration into Europe remains at the centre of heated political debates, 'citizens' (including charity workers, activists, volunteers etc.) who provide help to 'irregular migrants' increasingly face intimidation, repression and prosecution from state authorities. There has been a rise in high-profile cases such as French farmer Herrou sentenced to prison for facilitating irregular entry at the French-Italian border, and Spanish activist Helena Maleno, accused by both Spain and Morocco of smuggling migrants. The activities for which individuals (and organizations) can be prosecuted are diverse and whether such activities are criminal is often contested: giving a lift to migrants, providing food or shelter, preventing a plane used for deportation from taking off, helping migrants to cross borders without documents, rescuing people at sea etc. Activists have coined the term 'crimes of solidarity', arguing that repressive legislations have been deployed not only to sanction criminals (e.g. 'smugglers') who benefit financially, but also to potentially sanction anyone providing help and relief to migrants, in defiance of international norms of human rights. This study explores these illegalisation and criminalisation processes amongst volunteers, activists, practitioners and other citizens in Morocco and France, where Civil Society Organisations have denounced state repression against migrants trying to cross the sea to continue their journeys and those providing assistance to them. It brings to the fore the shifting boundaries between 'citizens' and 'irregular migrants' and debates over solidarity and illegality. Whilst scholars have increasingly paid attention to the production of illegality amongst migrants, there has been little work on how such processes also affect the political agency and subjectivity of citizens. The study will address this gap by generating qualitative data on how citizens are subjected to and navigate illegalisation and criminalisation processes. It examines these processes in a European country (France) and one of its partners in the Global South (Morocco) for the 'management of migration'. This comparative approach enables to further highlight how hostile migration politics are entangled with a range of connections across Africa and Europe and competing discourses over values such as solidarity. To address the methodological and ethical issues which emerge from researching such politically contentious matters, this ethnographic study will combine participant-observation and interviews with visual methods to generate outputs with transformative power. Co-designed and co-delivered with civil society partners to ensure cross-sector relevance, the project includes two Knowledge Exchange and Impact events (in France and in Morocco) to bring together practitioners, activists, researchers, artists and policy-makers. These events will foster wider cross-sector collaborations through the sharing of best practice and solutions to the criminalisation of solidarity towards migrants. The KEI events will include the launch of country-specific policy briefs about: the legal framework and risks faced by activists; testimonials and evidence-based policy recommendations on practices and policies. The policy briefs will be aimed to relevant state bodies and decision-makers and other research users in France, Morocco and beyond. The project will also entail one international workshop in Manchester with delegates from across and beyond academia to share findings and responses to the criminalisation of acts of solidarity towards irregular migrants in Europe and the...